2018
DOI: 10.1159/000493626
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oral Microbiota Revealed High Abundance of Prevotella Intermedia in Gout Patients

Abstract: Background/Aims: Microbes reside in a number of body sites, including the oral cavity, and are associated with the progression of many systemic diseases. In this study, we aimed to investigate the effects of gout and hyperuricemia (HUA) on the composition of oral microbiomes. Methods: Analysis of the oral microbiota from 12 gout patients, 11 HUA patients, and 19 healthy control subjects was performed using a deep sequencing approach, and validation of significant changes in Prevotella intermedia and Serratia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
4
31
0
1
Order By: Relevance
“…Systemic diseases can affect the oral microbiome significantly [13]. It has been found that certain diseases often modify the existing microflora of the oral cavity, as shown in a study on patients of gout and hyperuricemia [12]. In this study, it was seen that the predominant microflora of the oral cavity in these group of patients as compared to healthy controls was salivary Prevotella intermedia and lower levels of Serratiamarcescens.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Systemic diseases can affect the oral microbiome significantly [13]. It has been found that certain diseases often modify the existing microflora of the oral cavity, as shown in a study on patients of gout and hyperuricemia [12]. In this study, it was seen that the predominant microflora of the oral cavity in these group of patients as compared to healthy controls was salivary Prevotella intermedia and lower levels of Serratiamarcescens.…”
Section: Introductionmentioning
confidence: 63%
“…There is a crosstalk between the host and the microbiota, which is highly influenced by various factors like lifestyle and behaviors, tobacco consumption, oral hygiene, use of antibiotics, and the industrial revolution [10, 11]. The oral microbiota plays critical roles in protecting against colonization by extrinsic harmful bacteria [12]. Systemic diseases can affect the oral microbiome significantly [13].…”
Section: Introductionmentioning
confidence: 99%
“…Prevotella was also observed to be increased in patients with reflux esophagitis (RE) and BE (Liu et al, 2013). Several studies suggested that increased abundance of Prevotella in the oral cavity was associated with many diseases (Asakawa et al, 2018;Flemer et al, 2018;Liu et al, 2018;Wu et al, 2018;Yang et al, 2019), suggesting that it might be a promising biomarker for the occurrence of EC. In our study, the increase of Prevotella abundance was only significant at the genus level and family level.…”
Section: Discussionmentioning
confidence: 99%
“…Although a Bacteroides-dominated microbiome is more common, Prevotella are present at > 10% relative abundance in the stool of 10%-25% of healthy American and European individuals (Koren et al, 2013). Compared with at least 25 species of Prevotella in the oral cavity, and at least 17 species of intestinal Bacteroides, only five Prevotella species have been reported in human intestine of which Prevotella copri (P. copri) was the most abundant (Accetto and Avgu stin, 2015;Ferrocino et al, 2015;Ibrahim et al, 2017;Li et al, 2009;Lin et al, 2013;Liu et al, 2018). Although mechanistic models of metabolism, growth, and colonization have been established for several intestinal Bacteroides and oral Prevotella spp., studies of intestinal Prevotella have lacked experimental tools and relied heavily on only two type strains, Prevotella copri and Prevotella stercorea (Hayashi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%